Pentingnya Legalitas dan Pemanfaatan Aset Waqaf (Wakaf Produktif) - Faizah, Zahratul; Azmi, Nora Mia; Lutfi Aisyah; Anggi Azhari (Bansigom Na Publisher, 2024)
This article discusses the importance of legality and the utilization of waqf assets in the context of productive waqf. Waqf, as one of the Islamic financial instruments, has significant potential to support social and economic development in society. However, the optimization of waqf assets is often hindered by legal issues and a lack of understanding regarding effective management. This study examines the legal aspects governing waqf in Indonesia, including the challenges and opportunities encountered in the legalization process of waqf assets. Furthermore, the article highlights the importance of professional management in the utilization of waqf assets to provide sustainable benefits for the community. Through a juridical analysis approach and case studies, this article concludes that strengthening the legality aspects and the productive utilization of waqf assets is key to maximizing the contribution of waqf to social and economic welfare.